Long hops : making sense of bird migration - Denny, Mark, 1953- (A Latitude 20 Book, 2016)
In Long Hops, physicist Mark Denny explains, in a clear, conversational style, the science of bird migration--from the intricacies of bird aeronautics to the newly unraveled mysteries of their magnetic compasses. While providing wherever possible examples of indigenous Hawaiian species, the book surveys the migration phenomenon as a whole, showing that birds are breathtaking works of engineering with spectacular capabilities for long-distance flights. Each year thousands of these hardy migrants fly 2,500 miles nonstop from Alaska to Hawai'i. How do they endure such marathon journeys, and how on earth do they know which direction to travel over featureless ocean? In fact, many migratory journeys, in all parts of the world and performed by birds as small as warblers and as large as swans, cover much longer distances. After answering the "who, why, where, when" questions, Denny focuses on the questions of how: how researchers study bird migration; how they gather data from old-fashioned bird banding, high-tech satellite tracking, and other techniques; and--above all--how the birds do it. Throughout the book, concepts such as the physics of bird flight and the role of physical geography on navigation are explained in a relatively math-free way. Denny also examines past adaptations migrating birds have made to changing environments and the challenges they face in the future, as the world beneath them faces rapid climate change exacerbated by human activity